Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1002/ange.19961082229
|View full text |Cite
|
Sign up to set email alerts
|

Tumorselektiv aktivierbare Prodrugs des Cytostaticums CC‐1065

Abstract: Die O‐Glycoside l des seco‐CI‐Derivats 2, das die seco‐Form der pharmakophoren Gruppe des cytotoxisch hochwirksamen Antibioticums CC–1065 ist, weisen nur eine sehr geringe Toxizität auf. In der tumorselektiven Krebstherapie können sie mit Konjugaten aus Glycohydrolasen und monoklonalen Antikörpern, die an tumorassoziierte Antigene binden, eingesetzt werden. Die Glycohydrolasen spalten die Prodrugs 1 unter Freisetzung der cytotoxischen Komponente 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 26 publications
0
15
0
2
Order By: Relevance
“…Since serum-free incubation medium was employed, any enzyme activity of the medium (as observed in previous studies [12] with other media) could be ruled out. We must therefore assume either that nonenzymatic cleavage of the glycosidic bond in 5 occurs, or that direct alkylation of the DNA with 5 takes place without formation of the spirocyclopropane moiety.…”
Section: Discussionmentioning
confidence: 99%
“…Since serum-free incubation medium was employed, any enzyme activity of the medium (as observed in previous studies [12] with other media) could be ruled out. We must therefore assume either that nonenzymatic cleavage of the glycosidic bond in 5 occurs, or that direct alkylation of the DNA with 5 takes place without formation of the spirocyclopropane moiety.…”
Section: Discussionmentioning
confidence: 99%
“…[21] Some time ago we demonstrated that the formation of the spirocyclopropane moiety as the pharmacophoric group of CC-1065 from a corresponding seco compound can be halted by transforming its phenolic hydroxy group into a glycoside. [22] Such a derivative can be hydrolysed enzymatically with a glycohydrolase, which liberates the drug. Thus, the glycosidic seco compound 2 bearing a bisindolyl car-as part of the 5-alkoxy substituent or at another position of the indole moiety, retain or enhance the cytotoxicity of the parent drug and provide an increased water solubility.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Such a derivative can be hydrolyzed enzymatically using a glycohydrolase which liberates the drug. In this way, glycosidic seco-CBI-Q 3 and similar compounds bearing a bisindolyl carboxylic acid moiety as a DNA-binding subunit were developed by us for ADEPT.…”
Section: Introductionmentioning
confidence: 99%